Cultural Study of Fisherman Community in The Settlement, Brondong, Lamongan, East Java - Wiwik Widyo Widjajanti; Antariksa; Amin Setyo Leksono; A.Tutut Subadyo (Nusantara Science and Technology Proceedings)
The fishing community is a society with low income socio-economic conditions, poverty of fishing communities originating from weak human potential and lack of environmental support in utilizing the natural potential and available resources. With the specific cultural characteristics of fishing communities, it does not always support increasing the potential of its citizens, sometimes even hampering the progress of the community itself. Fishermen communities pay less attention to their settlement environment, fishermen's neighborhood conditions look bad, it requires structuring fishermen's neighborhoods, especially the existence of open spaces. The aim of the study was to identify and analyze the cultural characteristics of the community in the fishing village, as a basis for efforts to arrange open space settlements. With compliance with open space, this can improve the quality of the environment and the standard of living of fisherman families on the coast. The research method used is a combination of qualitative and quantitative research with a phenomenological approach, a research area on the North Coast of East Java, by sampling the Brondong coastal fishing village in Lamongan. The research was conducted by identifying and comprehensive studies of cultural aspects of fishing communities in the coastal area. It is expected that the results of this study can provide a discourse on government policy regarding the implementation of open space procurement, taking into account the culture of fishing communities, so that it can produce a concept of open space that can significantly spur economic and social growth of fishing communities on the coast.